New modified filler obtained by silica formed by sol–gel method on calcium carbonate - José A. F., Gamelas (2011)
This study focus on the modification of the particles of precipitated calcium carbonate (PCC) with silica formed in situ by sol–gel method. The new materials were characterized by several spectroscopic, analytical and microscopic techniques. A dense film of highly branched silica was formed at the surface of the scalenohedral PCC crystals. The amount of silica deposited at the PCC surface, as determined by thermogravimetric analysis, reached up to 25 wt% under appropriate experimental conditions. Particle size distributions obtained by laser diffraction spectroscopy of the new modified PCC’s were close to the distribution of the original PCC, even considering that some variation in the average size of the particles was noted. This result is of great interest regarding the application of these materials, for instance, as fillers in the paper industry since the coating of silica may contribute to the fibre-to-fibre bonding, thus improving paper strength.